PEMBERDAYAAN MASYARAKAT PEDULI STROKE DENGAN PEMBENTUKAN RINTISAN PUSAT HOME CARE STROKE DAN PELATIHAN HOME CARE STROKE DI KOTA TRENGGALEK - hariyanto, awan; Christiani, Mimik; Niningasih, Rahayu (Politeknik Kesehatan Kemenkes malang, 2024)
Stroke is a disease with a sudden onset and causes death and disability both in urban and rural areas. The consequences of a stroke in the community include paralysis of the upper and lower limbs, vision problems, difficulty speaking and difficulty swallowing, while the psychological impacts that can occur are frustration and irritability. Stroke home care services providing nursing care to stroke patients after post-hospital treatment with home care are very much needed by the family. This community service method includes holding Focus Group Discussions with stakeholders and training for stroke home care cadre participants. The offline home care stroke training method of bedside teaching is very effective in increasing knowledge and care skills for stroke patients from 12 cadre participants. After the training, 91.6% of cadre participants' knowledge of skills improved well. From the results of the Focus Group Discussion, the formation of stroke home care is really needed in society in form health facilities with permits in accordance with applicable regulations. Empowerment of the Stroke Care Community in Efforts to Establish Stroke Home Care which is carried out through training is very effective in increasing knowledge and understanding skills in stroke home care care and its establishment and operation requires in the form of health facilities with permits in accordance with applicable regulations.